Penerapan Akuntansi Berbasis Syariah dalam Lembaga Amil Zakat Nasional Yatim Mandiri - Mulyani Rizki; Vania Gustriana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Sharia accounting has become a substitute concept for conventional accounting. The concept of sharia accounting not only prioritizes management and capital owners, but also prioritizes other parties, such as consumers, society and even their responsibilities to God. A description of building a good business and being able to contribute by building a zakat-oriented entity. Zakat oriented makes an entity good if it can provide maximum zakat contributions, so that zakat oriented not only maximizes its profits but also how much the entity pays its zakat. But the value of the zakat must be based on the assets or wealth owned by the entity obtained in a halal manner. The purpose of this study was to determine whether the Zakat Financial Report at LAZNAS Yatim Mandiri Palembang Branch was in accordance with PSAK No. 109. This study was conducted to test the financial reports prepared by LAZNAS Yatim Mandiri Palembang in accordance with PSAK No. 109 concerning Zakat Accounting. According to the findings obtained from this study, it was concluded that Yatim Mandiri Palembang as one of the National Zakat Amil Institutions (LAZNAS) had fully implemented the use of PSAK No. 109. In presenting financial statements. Because in PSAK No. 109, zakat accounting aims to regulate the recognition, measurement, presentation and disclosure of zakat, infaq/sadaqah transactions.